Close encounters of the US kind: illness and injury among US athletes at the PyeongChang 2018 Winter Olympic Games - Nabhan, D.; Windt, J.; Taylor, D.; Moreau, W. (British Journal of Sports Medicine, 2020)
Aim To describe injury and illness incidence during the 2018 Winter Olympic Games (WOG) by Team USA.